A Rational Approach to Operative Obstetrics - Hannah, Walter J. (1971)
In this article Dr. Hannah outlines a philosophy of operative obstetrics which, he says, “seems to me to possess the supreme virtue of safety to mother and fetus, and, to paraphrase the words of a contemporary brewery commercial... that's what obstetrics is all about.”